The effect of sugarcane fiber length and fiber volume fraction on NaOH immersion with polyester matrix on impact test strength - Azaki Azlan; Juanda, Juanda; Zaldy Kurniawan, Zaldy Kurniawan (JTTM : Jurnal Terapan Teknik Mesin, 2026)
Sugarcane bagasse waste is an abundant byproduct of the sugar industry in Indonesia and has the potential to be used as an environmentally friendly composite reinforcement material. This study was conducted to examine the effect of sugarcane fiber length and fiber volume fraction on the impact strength of polyester resin-based composites after alkali treatment using 5% NaOH solution. The specimen manufacturing process was carried out using the hand lay-up method using variations in fiber lengths of 50 mm, 60 mm, and 70 mm and fiber volume fractions of 7%, 10%, and 13%. Impact strength testing was carried out using the Charpy method according to ISO 179-1 standards at the Mechanical Engineering Laboratory of the Bangka Belitung State Manufacturing Polytechnic. Data analysis was carried out using a two-factor factorial experimental design to determine the effect of each variable and its interaction on the impact strength value. The results showed that fiber length and volume fraction had a significant effect on the material's ability to absorb impact energy. The best combination was obtained at a fiber length of 70 mm and a volume fraction of 13% with an average impact strength of 52.2 kJ/m², while the lowest value of 27.7 kJ/m² was found at a fiber length of 60 mm with a volume fraction of 7%. This value exceeds the impact strength standard for high-impact ABS plastic car dashboards of 13.48 kJ/m². Thus, sugarcane fiber-reinforced composites have the potential to be developed as an environmentally friendly alternative material for automotive components, particularly car dashboards.